Development and Validation of a Mathematical Model to Predict the Complexity of FMR1 Allele Combinations - Rodrigues, Bárbara; Vale-Fernandes, Emídio; Maia, Nuno; Santos, Flávia; Marques, Isabel; Santos, Rosário; Nogueira, António J. A.; Jorge, Paula (Frontiers in Genetics, 2020)
The polymorphic trinucleotide repetitive region in the FMR1 gene 5’UTR contains AGG interspersions within the CGG repeat tract, particularly in normal-sized alleles (CGG<45). In this range repetitive stretches are typically interrupted once or twice, although alleles without or with three or more AGG interspersions can also be observed. AGG interspersions together with the total length of the repetitive region confer stability and hinder expansion to pathogenic ranges: either premutation (55